Anesthesia: A Poetic Journey through Silence and Science - Park, Nadia (Science Insights, 2025)
Beneath the lights of silver hue, Where voices soften, fading too, A breath is drawn, a mask is near— “Just count to ten, there's naught to fear.” The world begins to twist and slide, As reason slips beneath the tide. A hush descends, the soul is free— Welcome now to anesthesia.